Antimicrobial activity of Pantanal macrophytes against multidrug resistant bacteria shows potential for improving nature-based solutions - Takahashi, Karen Midori; Nakasato, Juliano Akio; de Jesus, Genilson Silva; Micheletti, Ana Camila; Pott, Arnildo; Yoshida, Nídia Cristiane; Paulo, Paula Loureiro (Plant stress (Amsterdam), 2024)
•Pantanal macrophytes contain bioactive compounds•P. acuminatum, S. virgata, and L. lagunae showed the most antibacterial activity•Plant extracts hold promise for combating antibiotic resistant bacterial strains The presence of macrophytes in constructed wetlands (CW) applied within the concept of nature-based solution (NBS) is crucial. Besides their role in the phytoremediation of pollutants, the cultivated plants, if properly selected, can also produce a range of bioactive compounds, including those with potential inhibitory effects against pathogenic bacteria. Bioactive compounds, such as flavonoids and ellagitannins, known for their remarkable antimicrobial properties, offer a sustainable solution to the global challenge of antibiotic resistance. In this study, we investigated macrophyte species adapted to the water variations in the Pantanal region (flood and dry seasons), focusing on those with both antimicrobial and ornamental potential, that could improve the ability of a CW system to treat greywater. Seven different macrophyte species were collected, cultivated, and evaluated for their antimicrobial activity (AA) against five standard bacterial strains and five multidrug-resistant clinical bacterial strains. Extracts from the leaf, stem, and root of Polygonum acuminatum showed the best AA against clinical multidrug-resistant strains of Staphylococcus aureus, Enterococcus faecium, and Escherichia coli, with minimum inhibitory concentration (MIC) values ranging from 78.13 to 312.5 µg.mL−1. Furthermore, the leaves of Ludwigia lagunae and P. acuminatum also showed considerable AA against standard strains of Enterococcus faecalis (MIC = 19.5 and 39.06 µg.mL−1, respectively) and Pseudomonas aeruginosa (MIC = 156.25 µg.mL−1 for both). High-Performance Liquid Chromatography with Ultraviolet and Mass Spectrometry analysis of these extracts identified important bioactive compounds, including flavonoids (quercetin 3-rhamnoside, hydropiperoside, quercetin 3-O-rutinoside, quercetin, myricetin 3-O-rhamnoside, kaempferol 3-O-rhamnoside, formononetin, and calycosin) and ellagitannins (3,3′4-tri-O-methylelagic acid, galloys-HHDP-glucose, and ellagic acid), along with other bioactive compounds. These results indicate that P. acuminatum and L. lagunae hold potential for application in CW owing to their antimicrobial property, local adaptability, and ornamental appeal.